2017
DOI: 10.1002/jemt.22849
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of dental enamel loss after debonding braces by analytical scanning electron microscopy (SEM)

Abstract: Clinical procedures when shear forces are applied to brackets suggest adhesion forces between 2.8 and 10.0 MPa as appropriate. In this study dental enamel was evaluated by scanning electron microscopy (SEM) before and after removing the brackets. Thirty bicuspids (previous prophylaxis) with metallic brackets (Roth Inovation 0.022 GAC), Transbond Plus SEP 3M Unitek adhesive and Transbond XT 3M resin were used. The samples were preserved to 37°C during 24 hr and submited to tangential forces with the Instron Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…SBS values higher than 11.3 MPa can cause fissures in the enamel surface and values lower than 7.3 MPa are less likely to cause enamel fissures (Bishara et al, 1995). Even though another study concurs with the adequate clinically values, it was observed enamel loss and therefore there is no relationship between the SBS and enamel loss (Rodríguez‐Chávez, Arenas‐Alatorre, & Belio‐Reyes, 2017). The reported values for a conventional adhesives range from 10.4 to 11.8 MPa (Bishara, VonWald, Laffoon, & Warren, 2001).…”
Section: Introductionmentioning
confidence: 84%
“…SBS values higher than 11.3 MPa can cause fissures in the enamel surface and values lower than 7.3 MPa are less likely to cause enamel fissures (Bishara et al, 1995). Even though another study concurs with the adequate clinically values, it was observed enamel loss and therefore there is no relationship between the SBS and enamel loss (Rodríguez‐Chávez, Arenas‐Alatorre, & Belio‐Reyes, 2017). The reported values for a conventional adhesives range from 10.4 to 11.8 MPa (Bishara, VonWald, Laffoon, & Warren, 2001).…”
Section: Introductionmentioning
confidence: 84%
“…The literature reports several methods for investigating the surfaces of enamel [19,[23][24][25][26][27][28]. As a result of the quantitative data provided, atomic force microscopy, environmental SEM, a profilometer, energy dispersive X-ray spectroscopy, and in vivo confocal microscopy analysis were used for these studies [29][30][31]. In particular, atomic force microscopy allows the morphological and mechanical properties of dental tissue surfaces with no peculiar treatment to be investigated [32].…”
Section: Discussionmentioning
confidence: 99%
“…Endo et al (2009) found that values of SBS between 2.80 and 10.00 MPa did not cause damage or enamel loss [22]. Rodriguez-Chavez et al (2017) found that even with SBS values as low as 6.8 MPa, it is possible to observe damage and enamel loss [23]. Enamel tearing could be observed when SBS values were higher than 13.8 MPa [24].…”
Section: Shear Bond Strengthmentioning
confidence: 99%